Find the solution to the equations. 2x - y = -3 x + y = 0 (0, 0), (-1, 1), (1, -1),

Original conversation

User: Find the solution to the equations.
2x - y = -3
x + y = 0
(0, 0),
(-1, 1),
(1, -1),

Weegy: A.(0, 0) is the answer. x=0, y=0 migzptz|Points 7632|

User: 5x + 10y = 18
x = y - 6
Which of the following equations is the result of substituting y - 6 in for x in the first equation?
5x + 10y - 6 = 18,
5y - 6 + 10y = 18,
5y - 30 + 10y = 18,

5x + 10y = 18 x = y - 6, replace x in the first equation we get: 5(y - 6) + 10y = 18 so, the result of substituting y - 6 in for x in the first equation is 5y - 30 + 10y = 18

Weegy: y=-3/4x+7/4 is the equation of the line that passes through (5, -2) and (-3, 4). User: (12x 2 - 10x -12) ÷ (3x + 2) Weegy: When you multiply and simplify (x + 4)(x^2 - 3x + 2) you get the result of x^3 + x^2 - 10x + 8. (More)

There are no comments.